Theoretical Analysis of The Super-Gaussian Pulse Propagation in Solid-Core Photonic Crystal Fiber - Al-Taie, Mohammed Salim Jasim (Journal of natural sciences, life and applied sciences, 2022)
Fiber optics have been greatly enhanced by photonic crystal fibers based on microstructure air-glass designs. On the one hand, such fibers enable highly tight light confine in a small mode shape region, resulting in significantly improved alternative options between light and dielectric medium. Photonic crystal fibers, on the other hand, allow light to be guided via air cores instead of glass. As a result, the latter form of fiber decreases of optical nonlinearities in ways that classic fiber designs cannot. The chirp effect and dispersion of photonic crystal fibers with super-Gaussian pulses during various pulses durations are examined in this paper. In both normal and anomalous dispersion patterns. As done the chirp effect and fiber dispersive nonlinear effects are investigated. For this study, the mathematical model of the solution of nonlinear equation is split-step Fourier method. The peak power reduces for broad pulses. When the magnitude of the super-Gaussian pulse increasing proportion, the pulse constriction is also noticeable, Furthermore, these results disclose important facts, such as the fact that an anomalous dispersion system is superior to a regular dispersion system for pulse. These findings are incredibly useful in learning more about photonic crystal fiber and improving data speeds in modern optical communication systems.